Physical seed dormancy in pea is genetically separable from seed coat thickness and roughness - Owen R. Williams; Jacqueline K. Vander Schoor; Jacqueline K. Vander Schoor; Jakob B. Butler; Jakob B. Butler; Valérie F. G. Hecht; James L. Weller; James L. Weller (Frontiers in Plant Science, 2024)
IntroductionThe seeds of wild pea (Pisum) exhibit marked physical dormancy due to impermeability of the seed coat to water, and the loss of this dormancy is thought to have been critical for domestication. Wild pea seed coats are also notably thick and rough, traits that have also reduced during domestication and are anecdotally linked to increased permeability. However, how these traits specifically interact with permeability is unclear.MethodsTo investigate this, we examined the genetic control of differences in seed coat characteristics between wild P. sativum ssp. humile and a non-dormant domesticated P. s. sativum accession in a recombinant inbred population. QTL effects were confirmed and their locations refined in segregating F4/5 populations.ResultsIn this population we found a moderate correlation between testa thickness and permeability, and identified loci that affect them independently, suggesting no close functional association. However, the major loci affecting both testa thickness and permeability collocated closely with Mendel’s pigmentation locus A, suggesting flavonoid compounds under its control might contribute significantly to both traits. We also show that seed coat roughness is oligogenic in this population, with the major locus independent of both testa thickness and permeability, suggesting selection for smooth seed was unlikely to be due to effects on either of these traits.DiscussionResults indicate loss of seed coat dormancy during domestication was not primarily driven by reduced testa thickness or smooth seededness. The close association between major permeability and thickness QTL and Mendel’s 'A' warrant further study, particularly regarding the role of flavonoids.